ALTERNATIVE METHODOLOGY OF THE ACCELERATED AGING TEST FOR RYEGRASS SEEDS - LOPES, Rodrigo Ramos; FRANKE, Lúcia Brandão; NUNES, Fabrício Silva (Scientia Agraria, 2009)
The present work aimed to study the methodology of accelerated aging test to evaluate ryegrass seeds physiological potential, as well as the efficiency of using salt saturated solution to control water absorption by the seeds during the test. Six ryegrass seed lots were used. The initial evaluation of these seed lots was by determining water content, germination tests and germination first counting. For the accelerated aging test, the traditional method (100% RU), the use of saturated saline solution (76% RU) and non saturated saline solution (94% RU) during 24, 48 and 72 h were employed. The experimental design was completely randomized, with six lots and four repetitions. The accelerated aging test with a saline solution is efficient to evaluate ryegrass seeds vigor, providing information equivalent to that of first germination counting and accelerated aging with water when performed at 40% of NaCl, 41 ºC for 24 h.